ANALISIS NILAI-NILAI PENDIDIKAN ISLAM DALAM PROSES TURUNNYA AL-QUR’AN - Khairan Muhammad Arif (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Research on islamic educational values in the process of descending the Qur'an is a study that aims to discuss and explore the wisdom or values of Islamic education conceived from the process of descending The Qur'an gradually and gradually and in accordance with the events experienced by the Prophet Muhammad saw and the muslims at that time. This research seeks to introduce the values of Islamic education from the process of descending the noble Qur'an to the world of Islamic education to be implemented in the learning process. The research method used in this study uses a qualitative method with an analytical description approach that aims to explain and describe the problems studied authentically, literatively and thematically, as well as scientifically analyze the object of research that give birth to conclusions. The source of this research is library (Library Research) , by tracing and examining classical and contemporary literature related to the history of the Qur'an, especially the process of the descent of the Qur'an. The results of this study are, first; The value of Islamic education in the process of the descent of the Qur'an gradually contains Islamic educational values that are moral in the nature of personal character (al-qiyam al-khuluqiyah ad-zatiyah) namely integrity personality in the form of patience and determination in the teaching and learning process. Second: Spiritual and priesthood Values (al-qiyam al-imaniyah), which must be instilled in the learners. Thirth: The character value of morality (al-qiyam al-akhulukiyah ad-dzatiyah). Fourth: Morality value of behavior/character (al-qiyam al-akhlakiyah as-sulukiyah) and Fifth: Value of social morality (al-qiyam al-akhlakiyah al-ijtima'iyah)